A Novel Method of Electric Scooter Torque Estimation Using the Space Vector Modulation Control - Chergui Hichem; Nasri Abdelfatah; Korhan Kayisli (International Journal of Renewable Energy Development, 2021)
In recent years, there are many studies have been conducted in the field of light electric vehicles, especially electric scooters. These are preferred in large urban areas that are crowded with cars and cause traffic congestion in the European and Asian continents. In this study, the three-wheel electric scooter contained two BLDC motors that drove the rear wheels and, each of these motors were controlled independently via an electronic differential. This paper aims to implement a Space Vector Modulation for the Direct Torque Control unit (SVM-DTC) of the BLDC wheel-motor of each driving wheel. The proposed system had been designed and simulated by using the MATLAB/SIMULINK environment. The performance of the overall system (scooter stability control system - energy storage system -power quality, etc.) with using SVM-DTC control was compared with the classical Direct Torque Control (DTC) algorithm by using the same electric scooter model. The obtained results showed clearly  the improvement made by the proposed control loop system at different stages, where it could reduce the THD of the stator current from 30.99% to 6.16%,as well as  it was able to achieve more than 0.2% of the charging state of the battery in 18 seconds only.